2022
DOI: 10.1371/journal.pone.0271100
|View full text |Cite
|
Sign up to set email alerts
|

Clinician-created educational video for shared decision-making in the outpatient management of acne

Abstract: Shared decision-making (SDM) provides patient-centered care. However, the limited consultation time was the main factor hindering the application. Patient education is crucial in the process of SDM. The use of visual aids as health education materials is an effective way to improve patients’ health literacy and medication adherence. This study aimed to determine the effectiveness of the clinician-created educational video of acne, accessed by patients during the waiting time, including knowledge level and sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Visual educational aids can effectively convey medical information and can supplement or replace text information [38 ▪ ]. Pediatric dermatology providers have few of this type of aid.…”
Section: Decreasing the Impact Of Limited Health Literacy: New Approa...mentioning
confidence: 99%
See 2 more Smart Citations
“…Visual educational aids can effectively convey medical information and can supplement or replace text information [38 ▪ ]. Pediatric dermatology providers have few of this type of aid.…”
Section: Decreasing the Impact Of Limited Health Literacy: New Approa...mentioning
confidence: 99%
“…Visual aids do not always have to be printed. Several studies have shown that educational videos can be used to increase patient knowledge and improve patients’ outcomes for certain dermatological conditions [38 ▪ ,39,40]. These informational videos were even preferred over traditional written materials by some patients [38 ▪ ].…”
Section: Decreasing the Impact Of Limited Health Literacy: New Approa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering all the above-mentioned information, proper education of the patient is of great importance. Regarding choosing a proper medium study by Hung et al [82] showed that a larger group of patients preferred educational videos over pamphlets. That is why educational videos are a useful tool in the education of patients about the treatment.…”
Section: Adherencementioning
confidence: 99%